Midnight in Paris [videorecording (Blu-Ray)] - Bates, Kathy, 1948-; Brody, Adrien; Bruni, Carla; Cotillard, Marion, 1975-; McAdams, Rachel, 1978-; Sheen, Michael; Wilson, Owen, 1968-; Aronson, Letty, 1943-; Tenenbaum, Stephen; Roures, Jaume; Allen, Woody, 1935-; Allen, Woody, 1935- (Sony Home Pictures Entertainment, 2011)
A romantic comedy about a family traveling to the French capital for business. The party includes a young engaged couple forced to confront the illusion that a life different from their own is better.